Jogo didático “Conecta Chronos”: o desenvolvimento e construção de um game destinado a museus e centros de ciências - Laryssa Cristine Cardoso Oliveira (2022)
Museums and science centers are undergoing a process of resignification, which is evidenced by the efforts these institutions have made to bring the public closer to Museums. Taking into account that current generations were born or grew up in contact with the advent of new technologies and that education needs to undergo transformations in order to serve this new audience, the digital natives, it becomes relevant to invest in new approaches and in new resources with the purpose of making the learning process more fruitful in these spaces and with possible repercussions in formal education spaces. In order to contribute to this purpose, this study aimed to develop a digital educational game for the Espaço do Conhecimento UFMG. Based on the Educational Digital Game Design models and recommendations for the development of games for museums, the Conecta Chronos game was created, which aims to dialogue with the permanent exhibitions for the destination place that relate to the Origin of Earth, Origin of Life, Evolution of Living Beings and Time Travel. The Conecta Chronos prototype is presented at the stage where the Game Design Document (GDD), maps, interface and game elements were developed for this initial version. Its implementation on the Espaço do Conhecimento UFMG website will allow it to be directed to the alpha phase, in which players and experts evaluate their experience with the game with the intention of finding problems that can be solved and, thus, undergoing improvements for their final validation. It is expected that the game can be installed as a totem in the Espaço do Conhecimento UFMG, but being a digital game available on the Internet, there is also provision for its use in formal education spaces and players' personal devices. The research developed aimed to produce a game consistent with the place it is intended for, providing experiences of playful, synesthetic, interactive and learning value, expanding the educational actions of that space. In addition, this work also contributed to expand the literature on educational digital games produced for Museums and Science Spaces and contribute to the process of developing games in other museum spaces.